Pain in preterm newborns submitted to music and 25% glucose intervention - Gleicia Martins de Melo; Maria Vera Lúcia Moreira Leitão Cardoso (Universidade Federal do Ceará, 2017)
to compare the pain response of preterm newborns submitted to arterial puncture who received musical intervention with those who received 25% glucose intervention. Methods: randomized, double-blind clinical trial; the sample consisted of 48 videos of preterm infants of the experimental group (music, n= 6), who listened to music for 10 minutes, and the control group (25% glucose, n=22), who received 25% glucose two minutes before puncture. The pain was evaluated by the Neonatal Facial Coding System at moments: Baseline, Treatment, Painful, Recovery 1 and Recovery 2. Results: there were similarities between groups at the moments Baseline, Recovery 1 and 2. A statistically significant difference was observed at the moment Treatment (p=0.014), Painful (p=0.029) for the control group. Conclusion: 25% glucose differed from music when comparing the pain response in the Treatment and Painful moments. Brazilian Registry of Clinical Trials: UTN: U1111-1123-4821.